Projected earnings accuracy and the profitability of stock recommendations - Dieter Hess; Daniel Kreutzmann; Oliver Pucker (University of Cologne, Centre for Financial Research (CFR), 2011)
Analysts providing more accurate earnings forecasts also issue more profitable recommendations. We demonstrate how investors can profit from this contemporaneous link by differentiating between able and lucky analysts. In line with previous studies, we find that past track records alone are not sufficient to identify profitable recommendations. Only skilled analysts working in a superior environment provide consistently profitable recommendations. The overall profitability of their recommendations is not driven by a post-announcement drift effect. We find that an implementable, i.e. look-ahead bias free, trading strategy based on the projected - rather than past - earnings accuracy yields substantial excess returns.
Keywords: G14; G17; G24; 330; analysts; portfolio management; profitability of recommendations